Deep Learning Self-Regulation Strategies of Indonesian Learners of English as a Foreign Language - Wahyuni B, Asti; Maneba, Sanaria; Syafitri, Nining (Institut Agama Islam Negeri Madura, 2025)
In many Indonesian EFL classrooms, students still rely on teacher-directed, exam-oriented routines with limited explicit instruction on self-regulated learning. Self-Regulated Learning (SRL) strategies are critical for academic success, especially in English as a Foreign Language (EFL) contexts. In Indonesia, however, there remains limited research on the deep learning self-regulation strategies used by EFL learners and the impact of gender and academic grade level. This study explores the deep learning self-regulation strategies Indonesian higher education students use in learning English, focusing on gender and grade level differences. Using the Deep Learning Strategies Questionnaire (DLS-Q) and semi-structured interviews, the results show a moderate use of SRL strategies, with Basic Learning Strategies being the most frequent. These strategies involve task planning, goal setting, and self-monitoring. Summarizing and activating prior knowledge were more often utilized by male students through Basic Learning and Deep Information Processing Strategies compared to female students. On the other hand, females appeared to prefer Social Strategies such as group discussions and collaboration with peers. These, along with the lack of variation with grade level, were not significant from a statistical standpoint. This research proposes that employing Deep Learning Self-Regulated Learning (SRL) strategies, using visuals and reflective tools, may enhance student engagement during EFL instruction.